Revision of the high-altitude genus Hyphinomos Uvarov, 1921 (Orthoptera: Tettigoniidae) with a redescription and new data on mating behavior and acoustic signals of H. svenhedini Ramme, 1950 - Ali, Ahsan; Jaiswara, Ranjana; Monaal; Kumar, Neelima R; Bharti, Umesh; Heller, Klaus-Gerhard (Zootaxa, 2022)
High mountains are known for their unique habitats and extreme climatic conditions. Many inhabitants of this area are specialists and are known as hypsobionts. Among Ensifera, only selected species from different genera are true hypsobionts. Species in the genus Hyphinomos are one of them. Hyphinomos occurs only between 3800 and 5500 m a.s.l., and is known from two species,  fasciata Uvarov, 1921 and svenhedini Ramme, 1950. Until recently they were both known only from their type localities situated in mountain ranges of the Himalayas. In this paper, we amend the description of H. svenhedini by adding new data on its distribution, habitat, structure of the male genitalia, stridulatory structures, acoustic signals (long-distance and courtship), and mating behavior. In addition, we have revised the description of Hyphinomos.